2015
DOI: 10.1111/pace.12610
|View full text |Cite
|
Sign up to set email alerts
|

Association of BNP and Troponin Levels with Outcome among Cardiac Resynchronization Therapy Recipients

Abstract: Introduction We conducted a prospective multicenter study to assess the prognostic value of combined baseline pre-implant plasma levels of the biomarkers cardiac troponin T (TnT) and BNP among CRT-D recipients. Methods At CRT-D implant, patients were stratified based on detectable TnT (≥0.01 ng/ml) and elevated BNP (predefined as >440 pg/ml) levels. Patients were classified into 3 groups high (both detectable TnT and high BNP), intermediate (either detectable TnT or high BNP), or low (non-detectable TnT and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
(42 reference statements)
1
5
0
2
Order By: Relevance
“…Comprehensive investigations have been carried out on the biological role and the potential clinical applications of the natriuretic peptides. Many studies have shown that a significant decrease in BNP levels occurs after CRT, resulting in a good prognosis [17]. The results obtained in this study are comparable to those of the previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…Comprehensive investigations have been carried out on the biological role and the potential clinical applications of the natriuretic peptides. Many studies have shown that a significant decrease in BNP levels occurs after CRT, resulting in a good prognosis [17]. The results obtained in this study are comparable to those of the previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…Elevation of these peptides has a well-established role for prediction of mortality for both acute and chronic heart failure situations [ 35 , 36 ]. In the CRT setting, the evidence for baseline BNP levels to predict clinical outcome is ambiguous; higher levels of BNP pre-implant have been correlated to higher risk of 1 year adverse events post-implant by some investigators [ 37 , 38 ], but other studies have not shown any correlation of baseline BNP to CRT-response [ 39 ]. Most likely this is due to the fact that successful CRT treatment can occur regardless of baseline BNP levels, and depends on a number of factors unassociated with baseline BNP levels, hence the resynchronization effect (and clinical outcome) is hard to predict by this metric.…”
Section: Discussionmentioning
confidence: 99%
“…5 Further evidence for the usefulness of BNP as a predictor of the CRT response was obtained in a prospective follow-up study of 267 HF patients with an average LVEF of 25% ± 8% (mean þ SD) undergoing CRT-D implantation. 6 Both individually and in combination, baseline high-sensitivity troponin T (hsTnT) and BNP values-in a multivariate Cox regression model including age, NYHA class, LVEF, and QRS duration-were independent predictors of outcome, defined as death or HF hospitalization. A risk category based on the elevation of two, only one, or none of the investigated biomarkers, proved a significant predictor of outcome, with respective hazard ratios (HRs) of 7.34 [95% confidence interval (CI) 2.48-21.69] and 2.50 (95% CI 1.04-6.04) for high-and intermediate risk groups.…”
Section: Cardiac Biomarkers In Resynchronization Therapymentioning
confidence: 99%